Measurement of the branching fraction of the decay B + → π + π − ℓ + ν ℓ in fully reconstructed events at Belle - Bhardwaj, Vishal; Patra, Sourav (American Physical Society, 2021)
We present an analysis of the exclusive Bþ → πþπ−lþνl decay, where l represents an electron or a muon, with the assumption of charge-conjugation symmetry and lepton universality. The study exploits the full ϒð4SÞ data sample collected by the Belle detector, corresponding to 711 fb−1 of integrated luminosity. Events are selected by fully reconstructing one B meson in hadronic decay modes, subsequently determining the properties of the other B meson. We extract the signal yields using a binned maximum-likelihood fit to the missing-mass squared distribution in bins of the invariant mass of the two pions or the momentum transfer squared. We measure a total branching fraction of BðBþ → πþπ−lþνlÞ¼½22.7þ1.9 −1.6 ðstatÞ 3.5ðsystÞ × 10−5, where the uncertainties are statistical and systematic, respectively. This result is the first reported measurement of this decay.
Only IISER Mohali authors are available in the record
Keywords: Particles Decay; Bottom Quark